Pengaruh Akuntantabilitas, Transparansi, Partisipasi Masyarakat, Sumber Daya Manusia Pada Pengelolaan Alokasi Dana Desa di Kecamatan Pemayung Kabupaten Batang Hari - Cindy; Mansur, Fitrini; Hernando, Riski (Jurusan Akuntansi FEB Universitas Jambi, 2025)
This study aims to determine and analyze the influence of accountability, transparency, community participation, and human resources on the management of village fund allocation in Pemayung District, Batang Hari Regency. The population of this study was all residents of Pemayung District, Batang Hari Regency. The total sample in this study was 98 respondents using the Slovin formula, which uses the error rate or tolerance. Data analysis was carried out using multiple linear regression processed with the help of the SPSS version 27 program. The results showed that accountability had no effect on the management of village fund allocation, transparency had a significant positive effect on the management of village fund allocation, community participation had a significant positive effect on the management of village fund allocation, and human resources had a significant positive effect on the management of village fund allocation. Simultaneously, accountability, transparency, community participation, and human resources had a significant positive effect on the management of village fund allocation.